GLOBAL SHEA NUT COMMODITY CHAINS AND POVERTY ERADICATION IN NORTHERN GHANA: MYTH OR REALITY? - Laube, W. (UDS International Journal of Development, 2016)
The increase in shea production, accompanied by the shea market restructuring, is often portrayed as an engine for rural transformation that will help end endemic poverty in Northern Ghana. In order to assess the actual impact and future promises of smallholder integration into the global shea commodity chain, this study undertook qualitative and quantitative research on shea pickers in the Upper East and Upper West regions. It looked at access to shea trees and nuts, forms and levels of production, marketing patterns and prices, as well as the local benefits from the shea trade. The research results show that the sale of shea nuts does provide a welcome source of income for rural women and poor rural households in Northern Ghana at a time of the year when resources are scarce. The sale of shea nuts therefore mitigates poverty to a considerable degree. But the findings also suggest that the low level of production and rather minuscule income from the shea nut trade cannot easily be raised by most shea pickers, as they face a limited labor supply and a reduction in access to shea trees. This makes it unlikely that the future of the shea nut trade will be a decisive factor in widespread poverty eradication, even if the price of shea nuts rose above current exploitative levels. This is also reflected in the behavior of rural women who tend to disengage from shea picking when more profitable economic activities such as independent farming, wage labor, or business opportunities arise. KEYWORDS: Global commodity chains, Northern Ghana, Poverty eradication, Shea nut trade, Smallholders